the Application of Classroom Management in English Language Teaching to Increase Students’ Speaking Ability at Tenth Grade of SMK Trisakti Bandar Lampung - Anita susanti (State Institute for Islamic Studies IAIN of Metro, 2017)
This research focused on the application of classroom management in English language teaching to increase students’ speaking ability at private vocational high school at Bandar Lampung. Data come from tenth class X accounting 1consists of35 students involving a writer and an English teacher. The research was conducted through a Classroom Action Research (CAR). The result showed that classroom management could be used to increase students’ speaking in learning English by implementing proper classroom management. Classroom management could be effective if it is supported by the ability of the teacher in managing a classroom. How teachers’ talk and behave are important factors in managing a class. Making a classroom climate was comfortable and condusive by proper classroom managing and adequate classroom facilities. The successful application of classroom management can be seen from the students’ positive response and their active participation in speaking learning activities.